Obeticholic acid treatment ameliorates the cardiac dysfunction in NASH mice - Szu-Yu Liu; Chia-Chang Huang; Ying-Ying Yang; Shiang-Fen Huang; Tzung-Yan Lee; Tzu-Hao Li; Ming-Chih Hou; Han-Chieh Lin (PLoS ONE, 2022)
Background Suppression of cardiac iinflammasome, which can be inhibited by Farnesoid X receptor (FXR) agonist, can ameliorate cardiac inflammation and fibrosis. Increased cardiac inflammasome decrease the abundance of regulatory T (Treg) cells and exacerbate cardiac dysfunction. Interaction between cardiomyocytes and Treg cells is involved in the development of nonalcoholic steatohepatitis (NASH)-related cardiac dysfunction. Aims This study evaluates whether the FXR agonist obeticholic acid (OCA) treatment improves NASH-associated cardiac dysfunction. Methods The in vivo and in vitro mechanisms and effects of two weeks of OCA treatment on inflammasome and Treg dysregulation-related cardiac dysfunction in NASH mice (NASH-OCA) at systemic, tissue and cellular levels were investigated. Results The OCA treatment suppressed the serum and cardiac inflammasome levels, reduced the cardiac infiltrated CD3+ T cells, increased the cardiac Treg-represented anti-inflammatory cytokines (IL-10/IL-10R) and improved cardiac inflammation, fibrosis and function [decreased left ventricle (LV) mass and increased fractional shortening (FS)] in NASH-OCA mice. The percentages of OCA-decreased cardiac fibrosis and OCA-increased FS were positively correlated with the percentage of OCA-increased levels of cardiac FXR and IL-10/IL-10R. In the Treg cells from NASH-OCA mice spleen, in comparison with the Treg cells of the NASH group, higher intracellular FXR but lower inflammasome levels, and more proliferative/active and less apoptotic cells were observed. Incubation of H9c2 cardiomyoblasts with Treg-NASHcm [supernatant of Treg from NASH mice as condition medium (cm)], increased inflammasome levels, decreased the proliferative/active cells, suppressed the intracellular FXR, and downregulated differentiation/contraction marker. The Treg-NASHcm-induced hypocontractility of H9c2 can be attenuated by co-incubation with OCA, and the OCA-related effects were abolished by siIL-10R pretreatment. Conclusions Chronic FXR activation with OCA is a potential strategy for activating IL-10/IL-10R signalling, reversing cardiac regulatory T cell dysfunction, and improving inflammasome-mediated NASH-related cardiac dysfunction.